EPIDEMIOLOGICAL ANALYSIS OF WOMEN WITH BREAST CANCER SUBMITTED TO BREAST RECONSTRUCTION IN A TERTIARY HOSPITAL IN PERNAMBUCO - Lima Filho, Darley Ferreira de; Ferreira, Nancy Cristina Ferraz de Lucena; Ferreira, Thais de Lucena (Mastology, 2026)
Objective: Breast reconstruction is a right assured by the public health system to patients submitted to mastectomy. However, there are factors that delay the performance of this procedure. This study aims to understand the epidemiological profile of women with breast cancer who underwent breast reconstruction in a reference hospital in the state of Pernambuco. Methods: This is an observational, retrospective research with an analytical character and descriptive approach. The data were collected through a questionnaire sociodemographic and clinical-surgical history of patients with breast carcinoma and then analyzed by the SPSS software version 18 with the percentages of the categories evaluated by the chi-square test, considering the significance level of 5%. The comparison of analyses was significant (p<0.005), showing that the profile described is the most frequent in the group of patients evaluated. CAAE: 42457420.1.0000.5193. Results: A non-probabilistic sample of 400 records was obtained in 10 years at a tertiary hospital in Recife (PE), most of them with a mean age between 46 and 59 years (45.3%), brown (61.1%), married (79.1%), with education until high school (60.7%), household professionals (45%), non-smokers (84.9%), who did not consume alcohol (94.9%), and had immediate reconstruction after mastectomy (70.3%). Conclusion: The findings support that patients with high educational levels are likely to undergo immediate breast reconstruction, pointing out that the socioeconomic level significantly influences the rates of breast reconstruction after mastectomy.